ARAH KEBIJAKAN INVESTASI INFRASTRUKTUR DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI REGIONAL DI INDONESIA - Wira Yudha Alam; Indah Rahmawati, Syela; Ainul Yaqin, Indra; Hakim Ali Madega, Erika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the uneven impact of infrastructure investment on regional economic growth in Indonesia, where some regions are able to capture the benefits of infrastructure development more quickly than others. The study aims to examine the direction of infrastructure investment policy in Indonesia and explain how such investment affects regional economic growth. This article applies a descriptive qualitative approach through literature review and policy document analysis, including the 2025–2029 National Medium-Term Development Plan, state budget documents, Statistics Indonesia publications, and national as well as international empirical studies on infrastructure and regional growth. The findings show that infrastructure investment contributes to regional growth by reducing logistics costs, improving interregional connectivity, expanding market access, increasing business productivity, and generating interregional spillover effects. However, these benefits are not evenly distributed. Regions with stronger economic bases, better institutional quality, and greater fiscal capacity tend to gain more rapidly than lagging regions. Roads, ports, airports, electricity, and digital infrastructure also produce different effects depending on each region’s economic structure. Therefore, infrastructure investment policy should emphasize project quality, intermodal connectivity, asset maintenance, blended financing, and integration with human capital development and local productive sectors. The study concludes that infrastructure investment is more effective in promoting regional economic growth when it is designed according to territorial needs rather than merely distributing physical projects across regions.